The Bench - Meghan, Duchess of Sussex, 1981-; Robinson, Christian (New York : Random House, 2021)
"Evoking a deep sense of warmth, connection, and compassion, The Bench gives readers a window into shared and enduring moments between a diverse group of fathers and sons--moments of peace and reflection, trust and belief, discovery and learning, and lasting comfort"--
Keywords: Fathers and sons -- Juvenile fiction; Benches -- Juvenile fiction; Stories in rhyme; Picture books; Fathers and sons -- Fiction; Benches -- Fiction; Picture books; Stories in rhyme; Picture books